Analysis of the Application of Subsurface Drip Fertigation Installation on the Growth Response of Lettuce Plants (Lactuca sativa L.) - Yuzanni, M Yusfan; Sumarsono, Joko; Abdullah, Sirajuddin Haji (Universitas Brawijaya, 2025)
Water resources are one of the important factors in the agricultural process. The availability of water in an area is strongly influenced by several factors such as climate, rainfall, regional topography, and land use change. Adoption of an effective and efficient irrigation system to support crop growth is needed. This study aims to design a subsurface drip fertigation system for lettuce crops and determine the response to cow urine fermentation fertilizer. The research method used is an experimental method with field experiments using subsurface drip fertigation. The research parameters were soil physical properties, emitter droplet uniformity, crop water requirements, soil wetting area, pressure head, storage water reduction, lettuce crop growth, and crop productivity. The results showed that the uniformity value of the emitter droplets before being applied to the field was 58.03%. At the same time, the emitter uniformity value after being applied to the area was 81.8%, which is classified as good and can be applied in the field to support the growth of lettuce crops. In addition, the wetting range and pressure values were 14.66 cm and 4.9 cm. The results of plant growth observations, such as the total leaf area of 60.5 cm, the average number of leaves of 5, and the crown width, which increased with the age of the plant, reached 9.8 cm. The fresh weight of the lettuce plants was 255 grams, and the average weight of the lettuce plants was 15.94 grams.